2019
DOI: 10.1158/1078-0432.ccr-18-1233
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Recurrent Malignant Glioma after Treatment Using Amide Proton Transfer-Weighted MR Imaging: A Validation Study with Image-Guided Stereotactic Biopsy

Abstract: Purpose: To quantify the accuracy of amide proton transfer-weighted (APTw) MRI for identifying active glioma after treatment via radiographically guided stereotactic tissue validation.Experimental Design: Twenty-one patients who were referred for surgery for MRI features concerning for tumor progression versus treatment effect underwent preoperative APTw imaging. Stereotactic biopsy samples were taken from regions of interest with varying APTw signal intensities. The relationship between final clinical patholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 51 publications
2
133
0
Order By: Relevance
“…) that true progression was associated with APTw hyperintensity, while pseudoprogression was associated with APTw isointensity to mild hyperintensity. A recent radiographically guided stereotactic biopsy study showed that APTw signal intensities were significantly higher in regions that represented active tumor than in regions that represented nonactive tumor, and that these two groups could be separated with an 85.1% sensitivity and a 94.1% specificity . This further supports the hypothesis that the APTw hyperintensity for active glioma can be used as a surrogate biomarker to differentiate recurrent tumor from treatment effects.…”
Section: Current Applicationsmentioning
confidence: 57%
See 3 more Smart Citations
“…) that true progression was associated with APTw hyperintensity, while pseudoprogression was associated with APTw isointensity to mild hyperintensity. A recent radiographically guided stereotactic biopsy study showed that APTw signal intensities were significantly higher in regions that represented active tumor than in regions that represented nonactive tumor, and that these two groups could be separated with an 85.1% sensitivity and a 94.1% specificity . This further supports the hypothesis that the APTw hyperintensity for active glioma can be used as a surrogate biomarker to differentiate recurrent tumor from treatment effects.…”
Section: Current Applicationsmentioning
confidence: 57%
“…Several clinical studies have now confirmed the ability of APTw imaging to differentiate recurrent tumor from treatment effects . These early results demonstrate the potential of APTw imaging in neuro‐oncology, providing a noninvasive imaging biomarker for distinguishing active tumor from radiation necrosis.…”
Section: Current Applicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…The CEST method can enhance the detection sensitivity of low‐concentration metabolites in vivo when repeated saturation transfer allows for an accumulation and amplification of the MRI signals derived from metabolite‐specific solute pools. Biomolecules that are detectable by various CEST techniques include polypeptides using amide proton transfer (APT), glycogen with “glycoCEST,” glycosaminoglycan by “gagCEST,” glutamate by “GluCEST,” glucose by “glucoCEST,” and creatine by “CrCEST.” Indeed, CEST MRI has been applied in patients with brain tumors, prostate cancer, breast cancer, and stroke using APT, osteoarthritis using gagCEST, epilepsy using GluCEST, and brain tumors using glucoCEST . Despite its great promise, the clinical use of CEST MRI is limited by the long acquisition times needed to acquire multiple frames at different saturation offset frequencies, and for quantification …”
Section: Introductionmentioning
confidence: 99%